Inluence of diferent aquatic materials on the perceived competence in the aquatic environment by students in the second cycle of early childhood education - Quintanilla Bautista, E.; Simón Piqueras, J. A.; León González, M. P.; Contreras Jordán, O. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The present work aimed to prove what didactic material resulted more effective for the development of perceived competence in the aquatic environment in 4 year-old children.To this end, the Pictorial Scale of Perceived Aquatic Competence was applied(Moreno & Ruiz, 2008), before and after an initiation program to the aquatic environment. In it, three didactic materials with different characteristics (Cuffs, Flotation Belt and Kiflot) were used as independent variables, and a sample of 18 children was included during seven sessions. The results showed that the material that allows greater freedom of movement and causes a more homogeneous flotation (Kiflot) obtains better results in perceived competition. Therefore, the need to use this type of material is concluded.